Optimizing the treatment of pain and anxiety in pediatric emergencies: the role of accreditation - Aaron Brody; Usha Sethuraman (Israel Journal of Health Policy Research, 2019)
Abstract Pervasive disparities exist in the treatment of pain and anxiety in pediatric patients presenting to hospitals with emergency conditions. This finding has been demonstrated worldwide, and is especially exacerbated in general emergency departments, which treat both adults and children. Policies to promote appropriate analgesia in the context of pediatric emergency care have been developed by several professional societies and governmental agencies in the United States; however, progress has been uneven, and data regarding these questions is lacking. In their excellent article, Capua and her co-authors address this precise problem through a unique methodology, by surveying nurse directors of both pediatric accredited and non-accredited emergency departments. Survey questions focused on availability of pharmacological and non-pharmacological modalities, and on the prevalence with which providers administered both oral and parenteral medications. The results demonstrated widespread availability of evidence based analgesic and anxiolytic treatment, ranging from medical clowns and specific holding positions, to use of intravenous opiates and conscious sedation. No significant differences were found associated with accreditation. These results are surprising and seem to call into question the value of pediatric accreditation. However, an alternative hypothesis would be that accreditation has succeeded, and the results reflect a large spillover effect, in which providers trained in accredited institutions bring these advanced practices to their local departments. Regionalization has been promoted for emergency care of many acute conditions such as trauma, stroke, and myocardial infarction. These results suggest that for pediatric emergencies, at least in regard to analgesia, the answer likely lies in dissemination of knowledge, rather than super specialization. In other words, bring the expertise to the children, not the children to the experts. Further research in this area could focus on optimal ways to achieve such knowledge translation.